2017
DOI: 10.1186/s12887-017-0828-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth of HIV-exposed uninfected, compared with HIV-unexposed, Zambian children: a longitudinal analysis from infancy to school age

Abstract: BackgroundEarly growth of HIV-exposed, uninfected (HEU) children is poorer than that of their HIV-unexposed, uninfected (HUU) counterparts but there is little longitudinal or longer term information about the growth effects of early HIV exposure.MethodsWe performed a longitudinal analysis to compare growth of HEU and HUU infants and children using data from two cohort studies in Lusaka, Zambia. Initially 207 HUU and 200 HEU infants from the Breastfeeding and Postpartum Health (BFPH) study and 580 HUU and 165 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 21 publications
(33 reference statements)
7
44
0
Order By: Relevance
“…The prevalence of undernutrition in the present study was higher in HEU infants compared to HUU infants during their first 1000 days. This is consistent with findings from a number of studies conducted in Zambia, Kenya, South-Africa, Uganda and Tanzania, which have demonstrated that HEU infants have poor growth compared to HUU infants (9,12,20,38,39) . A study in Kenyan infants found that HEU infants had poor nutritional Table 2 Feeding practices of infants by HIV exposure from selected districts in Botswana.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of undernutrition in the present study was higher in HEU infants compared to HUU infants during their first 1000 days. This is consistent with findings from a number of studies conducted in Zambia, Kenya, South-Africa, Uganda and Tanzania, which have demonstrated that HEU infants have poor growth compared to HUU infants (9,12,20,38,39) . A study in Kenyan infants found that HEU infants had poor nutritional Table 2 Feeding practices of infants by HIV exposure from selected districts in Botswana.…”
Section: Discussionsupporting
confidence: 91%
“…Without PMTCT strategies, HIV transmission from mother to child could be as high as 25% . However, this success has resulted in the increase in the population of HIV‐exposed but uninfected (HEU) infants . Health and/or nutritional issues unique to HEU infants will have major population health implications as their numbers increase .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical rationale for hypothesizing the link between the mother's infection and kid's growth is based on some observations made over last decades in pregnant women infected with human immunodeficiency virus (HIV) which is a close relative of SRLV. The growth of HIV-exposed but uninfected children seems to be impaired, mainly in the first 12-24 months of their life [18][19][20][21]. Pathogenesis of this phenomenon is not clear with a chronic immune activation in response to prolonged prenatal HIV exposure [22] or an exposure to antiretroviral drugs in utero and postnatally during breastfeeding [23] being the most likely culprits.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that infants who are HEU experience poorer growth, health and survival outcomes compared with their counterparts, infants who are HIV-unexposed (HU) [2][3][4][5][6][7]. Some studies have shown that fetal growth, measured by an infant's birth weight and length may be affected by in utero antiretroviral (ARV) exposure [6,[8][9][10]. Many studies demonstrated that in utero fetal exposure to HIV and ARVs is associated with adverse birth outcomes such as preterm birth, low birthweight and small-for gestational age [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%